Exposure to sun radiation as a risk factor for the occurrence of basal cell carcinoma in the Montenegrian population - Maksimović Nataša; Ražnatović Milena; Marinković Jelena; Janković Janko (Vojnosanitetski Pregled)
Backgound/aim: Basal cell carcinoma (BCC) is the most frequent form of carcinomas in the whites. Among the environmental factors, the most important risk factor for its occurrence is the exposure to sun radiation. The aim of this study was to assess the role of the sun radiation in the development of basal cell carcinoma BCC in the Montenegrian population. Methods. A case-control study was conducted in a period from 2002-2003. The study group included 100 histopatologically confirmed cases with BCC, while the control group included 100 patients from the same population, who did not present skin cancer and who were individually matched with the cases from the study group by sex and age (± 5 years). All the participants were interviewed using an epidemiological questionnaire. For statistical analysis, the χ2 test and univariate logistic regression analysis were used. Results. The risk for development of BCC was increased in the persons: that always had burns with no tan during the exposure to sunlight (OR = 1.75; 95% CI = 1.20-2.55; p = 0.003); that developed sunburns after two hours of the exposure to sunlight (OR = 3.72; 95% CI = 2.39-5.79; p < 0.001) that kept light tan or remained without changes in childhood and adolescence after the repeated exposures to sunlight (OR = 2.92; 95% CI = 1.89-4.52; p < 0.001) that often had severe and painful sunburns (OR = 4.48; 95% CI = 2.74-7.33; p < 0.001). Conclusion. Our study confirmed the significance of sunlight exposure for the development of BCC.